Digital Transformation of Photography Service Marketing on Instagram @premiumphotography_ph - Novitasari; Adiprabowo, Vani Dias (Institut Komunikasi dan Bisnis LSPR, 2024)
The rapid advancement of technology has made the emergence of many digital platforms make it easier to disseminate information. This study aims to find out marketing communication through Instagram social media on Instagram @premiumphotography_ph accounts. With this phenomenon, this study aims to find out marketing communication through Instagram social media on Instagram @premiumphotography_ph account. The reason for researching this is because it is interesting to discuss and in the digital era there are many significant changes related to life. The focus of the researcher here is Instagram social media, how they can use digital media to market photography services. This research method uses qualitative, data collection techniques through observation on Instagram social media accounts @premiumphotography_ph, observations and interviews. The result of this study is that photo and video vendors from Premium Photography Yogyakarta effectively use Instagram social media as a new platform to convey information related to their services to the public. They package their information in the form of stories and other interesting content published through the Stories feature and feeds on Instagram. The use of Instagram by @premiumphotography_ph accounts as a publication medium has proven its effectiveness in achieving their goals.